Highly thermal conductivity silicon nitride/carbon fibres/bismaleimide composites. Issue 2 (29th September 2014) - Xie, Chao; Han, Ying; Zhao, Ruoxi
Abstract : Hybrid fillers of silicon nitride/carbon fibres (Si3 N4 /CFs) are performed to improve the thermal conductivities, mechanical and thermal resistance properties of the bismaleimide (BMI) composites. The thermally conductive coefficient of the Si3 N4 /CFs/BMI composites is improved to 1.68 W/mK with 50 wt% modified Si3 N4 fillers. The flexural strength and interlaminar shear strength of the composites are optimal with 10 wt% modified Si3 N4 fillers. The thermal resistance properties of the Si3 N4 /CFs/BMI composites are also improved with the addition of Si3 N4 fillers. Surface modification of Si3 N4 fillers exhibits positive effects on the thermal conductivities and mechanical properties of the Si3 N4 /CFs/BMI composites. POLYM. COMPOS., 37:468–471, 2016. © 2014 Society of Plastics Engineers